MARKET AND DEVELOPMENT TRENDS IN COGENERATION AND COMBINED HEAT AND POWER PLANTS - Jan Slad; Andreas Pickard; Frank Strobelt (Acta Polytechnica CTU Proceedings, 2018)
The transition of energy mix in Europe is placing greater focus on energy efficiency. Lawmakers in some of EU countries have already recognized that combined heat and power generation (cogeneration, CHP) can help increase energy efficiency. Targeted promotion and subsidization have raised the cost-effective profitability of cogeneration plants significantly. But how can the economic value of this investment be maximized?